DESIGN OF A WEB-BASED ORDER MANAGEMENT APPLICATION FOR JF LEGAL NETWORK - Rozi, Fatchur; Tiarno, Setyono Ressly; Budhilaw, Ericsson; Rozi, Nanang Fakhur (Acitya Wisesa: Journal of Multidisciplinary Research, 2025)
JF Legal Network is an integrated enterprise operating at the intersection of the legal and business sectors. Its service portfolio includes accreditation and legal positioning services, specifically comprising Jakad Journals for article editing, Jakad Media for legal publishing and printing services, and a law firm. A significant operational challenge identified within the company is the complexity of its order management process. Currently, the recording of incoming and outgoing orders is conducted manually, which leads to inefficiencies and delays in generating order reports for management. To address this issue, this study proposes the development of a centralized web-based order management application. The system will be developed following the Software Development Life Cycle (SDLC) methodology, utilizing PHP, MySQL, and the Laravel framework. The primary objective of this system is to streamline the order recording process, thereby enhancing accuracy and timeliness in management reporting.